Utilizing network pharmacology to explore the underlying mechanism of Radix Salviae in diabetic retinopathy - Chun-Li Piao; Jin-Li Luo; De Jin; Cheng Tang; Li Wang; Feng-Mei Lian; Xiao-Lin Tong (BMC, 2019)
Abstract Introduction Radix Salviae (Dan-shen in pinyin), a classic Chinese herb, has been extensively used to treat diabetic retinopathy in clinical practice in China for many years. However, the pharmacological mechanisms of Radix Salviae remain vague. The aim of this study was to decrypt the underlying mechanisms of Radix Salviae in the treatment of diabetic retinopathy using a systems pharmacology approach. Methods A network pharmacology-based strategy was proposed to elucidate the underlying multi-component, multi-target, and multi-pathway mode of action of Radix Salviae against diabetic retinopathy. First, we collected putative targets of Radix Salviae based on the Traditional Chinese Medicine System Pharmacology database and a network of the interactions among the putative targets of Radix Salviae and known therapeutic targets of diabetic retinopathy was built. Then, two topological parameters, "degree" and "closeness certainty" were calculated to identify the major targets in the network. Furthermore, the major hubs were imported to the Database for Annotation, Visualization and Integrated Discovery to perform a pathway enrichment analysis. Results A total of 130 nodes, including 18 putative targets of Radix Salviae, were observed to be major hubs in terms of topological importance. The results of pathway enrichment analysis indicated that putative targets of Radix Salviae mostly participated in various pathways associated with angiogenesis, protein metabolism, inflammatory response, apoptosis, and cell proliferation. The putative targets of Radix Salviae (vascular endothelial growth factor, matrix metalloproteinases, plasminogen, insulin-like growth factor-1, and cyclooxygenase-2) were recognized as active factors involved in the main biological functions of treatment, which implied that these were involved in the underlying mechanisms of Radix Salviae on diabetic retinopathy. Conclusions Radix Salviae could alleviate diabetic retinopathy via the molecular mechanisms predicted by network pharmacology. This research demonstrates that the network pharmacology approach can be an effective tool to reveal the mechanisms of traditional Chinese medicine from a holistic perspective.